Dehydroepiandrosterone and Dehydroepiandrosterone Sulfate in Alzheimer's Disease: A Systematic Review and Meta-Analysis - Pan, Xiongfeng; Wu, Xinyin; Kaminga, Atipatsa C.; Wen, Shi Wu; Liu, Aizhong (Frontiers in Aging Neuroscience, 2019)
Background: Many theories of Alzheimer’s disease are based on evidence that dehydroepiandrosterone and dehydroepiandrosterone sulfate levels declines with age. Aims: To summarize research results on the association of dehydroepiandrosterone and dehydroepiandrosterone sulfate levels with Alzheimer’s disease. Method: Systematic searches were performed in March 2018 in the electronic databases of PubMed, Embase, Web of Science, and Psyc-ARTICLES for studies on the association of dehydroepiandrosterone and dehydroepiandrosterone sulfate levels with Alzheimer’s disease. Standardized mean difference was calculated to measure the strength of the association of dehydroepiandrosterone and dehydroepiandrosterone sulfate levels with Alzheimer’s disease, using random-effects model. Results: Thirty-one eligible studies were included in the final analysis. No statistically significant association between dehydroepiandrosterone level and Alzheimer’s disease was found (standardized mean difference: 0.51, 95% confidence interval: -0.44 to 1.45, Z=1.06, p=0.29). On the other hand, lower dehydroepiandrosterone sulfate level was observed in Alzheimer’s patients than in controls (standardized mean difference: -0.69, 95% confidence interval: -1.17 to -0.22, Z=-2.84, p<0.01). Conclusion: Dehydroepiandrosterone sulfate level in lower in Alzheimer’s patients than in healthy controls.